PWE-099 Direct Detection Of Thiopurine Metabolites In Erythrocytes And Leukocytes Using A Novel Lcms/ms Method To Interrogate Drug Response And in Vivo Metabolism. (9th June 2014) - Coulthard, SA; Berry, P; McGarrity, S; Redfern, CP; Ansari, A
Abstract : Introduction: One of the major issues hampering the understanding of metabolism and response to thiopurine drugs (azathioprine (Aza), mercaptopurine (MP) and thioguanine (TG)) is the indirect method for measuring their metabolites in red blood cells (RBC) after pre-analytical processing. RBC which lack inosine-monophosphate dehydrogenase, critical for bioconversion of thiopurines, do not reflect thiopurine metabolism in peripheral mononuclear cells (PMC)) as exemplified by the poor concordance between metabolite levels and clinical response. To address this problem we have developed a 'direct method' of measuring thiopurine metabolites in both RBC and PMC. Methods: PMCs and RBCs were isolated from blood samples of thiopurine (low dose aza/allopurinol (LDAA), TG or MP) treated patients. They were separated by Lymphoprep, sonicated, centrifuged and 50 uL of supernatant injected for chromatographical separation of the metabolites and analysed on a API4000 triple quadrupole LC-MS/MS. Standard curves and controls validated and metabolite levels reported as pM of metabolites/mg of protein. Results: Concentrations of metabolites in both RBC and PMCs were determined from standard curves (7.8 -500 nM) and expressed relative to protein concentration. Comparison between these and results from commercially available RBC metabolite levels are shown below. Sum of methylated metabolites from the LCMS/MS includes methylated thioguanine nucleotides. Undetected metabolites listed as ND Conclusion: The metabolite profiles between patients on FDA, LDAA and TG are very different indicating that these treatments have distinct metabolic pathways. The direct and commercial methods are also different in metabolic profiles raising the suspicion that the commercial method is not an accurate reflection of true metabolic profiles in RBCs. The clinical implication from these data is that the choice of drug protocol (LDAA in "high methylators") is not based on reliable methods. To confirm this, these data and other markers of response and efficacy are being collected prospectively to facilitate a more informed and deeper understanding of how and why FDA, LDAA and TG treated patients respond to these different drug protocols, with an ultimate goal of individualisation of therapy and improvement of the use of these cheap and established drugs. Disclosure of Interest: None Declared.